HDAC1 Cooperates with C/EBPα in the Inhibition of Liver Proliferation in Old Mice - Wang, Guo-Li (American Society for Biochemistry and Molecular Biology, 2008)
Epigenetic control of liver proliferation involves cooperation between transcription factors and chromatin-remodeling proteins. In this work, we found that the levels of HDAC1 (histone deacetylase 1) are increased in quiescent livers of old mice. The elevation of HDAC1 in liver is mediated by the RNA-binding protein CUGBP1. We found that the age-associated CUGBP1-eIF2 complex binds to the 5′ region of HDAC1 mRNA and increases translation of HDAC1 in the liver. Further analyses showed that CUGBP1 also increases expression of HDAC1 in cultured cells, in the livers of CUGBP1 transgenic mice, and in the livers of mice injected with cyclin D3, which enhances the formation of the CUGBP1-eIF2 complex. In livers of old mice, HDAC1 interacts with the transcription factor C/EBPα and is recruited by this protein to E2F-dependent promoters as a component of high M(r) C/EBPα-Brm complexes. The recruitment of HDAC1 to c-Myc and FoxM1B promoters leads to deacetylation of histone H3 at Lys-9 on these E2F-dependent promoters. We show that HDAC1 is an important mediator of growth-inhibitory activity of C/EBPα and that small interfering RNA-mediated inhibition of HDAC1 reduces the ability of C/EBPα to inhibit cell proliferation. In addition, we have found that both elevation of HDAC1 and interaction of C/EBPα with HDAC1 are controlled by cyclin D3-dependent mechanisms. Treatment of old mice with growth hormone, which reduces cyclin D3 levels, leads to the reduction of the CUGBP1-eIF2 complex, normalization of HDAC1 levels, and inhibition of interactions of HDAC1 with C/EBPα-Brm complexes. Thus, our data demonstrate that translational elevation of HDAC1 in livers of old mice is involved in the assembly of high M(r) protein-protein complexes that inhibit liver proliferation.